A geometria dedutiva em livros didáticos das escolas públicas do Estado de São Paulo para o 3° e 4° ciclos do Ensino Fundamental - Carlovich, Marisa (2005)
ABSTRACT This study aims at analysing the teaching-learning process of Deductive Geometry in school-books prepared to the 3rd and 4th cycles of Ensino Fundamental (from the 1st to the 8th degrees students usually from 7 to 15 years) used in state-run schools in Sao Paulo State from the 1990s to the present day. According to Chervel (1990), after an important change in the history of Education there follows a trend in the approach chosen for pedagogical handbooks. In the past decade, this significant change in the history of Brazilian Education concerning Mathematics was the implementation of Programa Nacional do Livro Didático National Programme for School Textbooks (PNLD), in 1995. That made us separate two periods for the purpose of analysis in our study: the early 1990s and the early 2000s periods respectively before and after this implementation. Our queries turned on how, in each period, school-books were close to the debates of Mathematical Didactics about the teaching-learning process of Deductive Geometry and on how the differences of views for each period took place.Results for the selected book sets printed in 1990s show signs of the Deductive Geometry approach in which demonstrations are presented to students and followed only by application exercises, typifying a practical teaching of Mathematics. Results for the selected book sets printed in the 2000s point to an optimistic view regarding the teaching of Deductive Geometry. In order to study Geometry properties, besides application exercises, students were asked to do the empirical and deductive validations, which typifies heuristic approach, according to Lakato s definition (1976). However, it is fundamental to show students the ways to master deductive reasoning in Geometry, as recommended by the theoretical studies of Mathematical Didactics, only partially attended to in the book sets analysed for the two given periods.